Activation of the Two-Component System LisRK Promotes Cell Adhesion and High Ampicillin Tolerance in Listeria monocytogenes - Aslan, Hüsnü; Petersen, Maiken Engelbrecht; De Berardinis, Alberto; Zacho Brunhede, Maja; Khan, Nasar; Vergara, Alberto; Kallipolitis, Birgitte; Meyer, Rikke Louise (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a foodborne pathogen which can survive in harsh environmental conditions. It responds to external stimuli through an array of two-component systems (TCS) that sense external cues. Several TCS, including LisRK, have been linked to Listeria’s ability to grow at slightly elevated antibiotic levels. The aim of this study was to determine if the TCS LisRK is also involved in acquiring the high antibiotic tolerance that is characteristic of persister cells. LisRK activates a response that leads to remodeling of the cell envelope, and we therefore hypothesized that activation of LisRK could also increase in the cells’ adhesiveness and initiate the first step in biofilm formation. We used a ΔlisR mutant to study antibiotic tolerance in the presence and absence of LisRK, and a GFP reporter strain to visualize the activation of LisRK in L. monocytogenes LO28 at a single-cell level. LisRK was activated in most cells in stationary phase cultures. Antimicrobial susceptibility tests showed that LisRK was required for the generation of ampicillin tolerance under these conditions. The wildtype strain tolerated exposure to ampicillin at 1,000 × inhibitory levels for 24 h, and the fraction of surviving cells was 20,000-fold higher in the wildtype strain compared to the ΔlisR mutant. The same protection was not offered to other antibiotics (vancomycin, gentamicin, tetracycline), and the mechanism for antibiotic tolerance is thus highly specific. Furthermore, quantification of bacterial attachment rates and attachment force also revealed that the absence of a functional LisRK rendered the cells less adhesive. Hence, LisRK TCS promotes multiple protective mechanisms simultaneously.